ETIOPATHOGENESIS AND DIGITAL APPROACHES IN THE DIAGNOSIS OF RETENTION OF UPPER PERMANENT CANINES. (LITERATURE REVIEW) (World Bulletin of Social Sciences, 2021)
The article describes the main reasons for the formation and formation of retention of the upper permanent canines. The author presented a literary review of the manuscripts, described in detail the entire cycle in the development of this pathology by both foreign and domestic scientists. Various methodologies for evaluating digital studies and modern approaches to therapy and planning for the treatment of retention of upper permanent canines, which are used in practice by an orthodontist, are also described